Autism and the criminal justice system: An analysis of 93 cases. Issue 5 (14th March 2022) - Slavny‐Cross, Rachel; Allison, Carrie; Griffiths, Sarah; Baron‐Cohen, Simon
Abstract: We investigate whether autistic people's vulnerability is taken into account at each stage of the criminal justice system (CJS). Defense lawyers from 12 nations were included in the study although the sample was predominantly from the UK. Lawyers completed an online survey regarding one case in which they had defended an autistic client between January 2015 and January 2020; and on one case in which they had defended a nonautistic client charged with a similar offense, to provide a comparison group. Ninety‐three lawyers (85% in the UK) reported on one autistic case, and 53 also reported on one nonautistic case. 75% of autistic clients were not given reasonable adjustments during the process. Only 43% were offered an appropriate adult during police investigations, even though they had an existing diagnosis of autism. 59% of prosecution barristers and 46% of judges said or did something during the trial that made the lawyers concerned that they did not have an adequate understanding of autism. Lawyers were 7.58 times more likely to be concerned about their autistic client's effective participation in court and were 3.83 times more likely to be concerned that their autistic clients would engage in self‐harm, compared with their nonautistic clients. There is a failure to identify and address autistic peoples' disability within the CJS. There is a need for mandatory autism training for police officers and the judiciary, with a focus on identifying autism and understanding the needs of autistic people so that reasonable adjustments are offered in all cases. Lay Summary: This study sought to investigate if the needs of autistic people are being overlooked by the police and other professionals within the CJS. Results show that autistic people are not always given the support they need during police questioning or in court. The experience of being involved with the police may also have a more negative impact on autistic peoples' mental health than that of nonautistic people.